The Correlation between Students' EMotional Intelligence and Their Academic Achievement in English Language at SMAN 1 Lawa - Agustini, Agustini; Kamaluddin, Kamaluddin; Nggawu, La Ode (Journal of Teaching English, 2019)
The study aims at investigating the correlation between students’ emotional intelligence and their academic achievement at the eleventh grade of SMA N 1 Lawa. The objective of the study was to answer the following research questions: what is the correlation between students’ emotional intelligence and their academic achievement in English language at SMAN 1 Lawa?. The study was correlation research study, which employed quantitative research methods. The data were collected from 135 participants who are from SMA N 1 Lawa class XI IPA and IPS. The data collection was carried out by using an emotional intelligence questionnaire and English achievement students from report card. Researcher used simple random sampling technique in taking the sample. The data of the study was analyzed through Spearman correlation analysis of SPSS 16. The result showed that the coefficient correlation that obtained from the computation was 0.352 and categorized as moderate correlation. The result showed that there was a positive correlation between students’ emotional intelligence and their academic achievement in English language. The conclusion of this study was drawn through the result of computation which showed that the value of coefficient of correlation (r) between two variables, that was emotional intelligence as the variable X and academic achievement as the variable Y, was as moderate as that of the Spearman correlation table with 0.05 level significant. Further, the data showed that there was a moderate correlation. Therefore, it showed that the alternative hypothesis is accepted and the null hypothesis was rejected.